The Umbrella Academy. Volume 2, Dallas - Way, Gerard (Umbrella Academy, 2009)
"The team is despondent following the near apocalypse created by one of their own and the death of their beloved mentor Pogo. So it's a great time for another catastrophic event to rouse the team into action. Trouble is -- each member of the team is distracted by some very real problems of their own. The White Violin is bedridden due to an unfortunate blow to the head. Rumor has lost her voice -- the source of her power. Spaceboy has eaten himself into a near-catatonic state, while Number Five dives into some shady dealings at the dog track and The Kraken starts looking at his littlest brother as the key to unraveling a mysterious series of massacres ... all leading to a blood-drenched face-off with maniacal assassins, and a plot to kill JFK!"--Publisher's web site.